Організаційно-економічний механізм підвищення ефективності управління водними ресурсами - Рижова, К.І.; Митрофанова, О.М. (Економіка природокористування і сталий розвиток, 2019)
Визначено принципи інтегрованого управління водними ресурсами у зрошуваному землеробстві. Розкрито сутність трансформацій управлінської системи, що передбачає передачу управління іригаційними мережами від державних структур до недержавних організацій. Запропоновано основні напрями вдосконалення економічного механізму розвитку меліорації. The necessity of a fundamentally new approach to the formation of a water management system and state regulation of water use has been proved in order to achieve sustainable water use parameters in the agricultural sector of the economy. The principles of integrated water management in irrigated agriculture are defined. It is shown that the formation of the model of integrated management in the water management and reclamation complex requires the introduction of organizational and economic innovations, changes in the institutional environment, transformations in the organizational structure of agricultural enterprises and public authorities. The essence of transformations of the irrigated agriculture management system is disclosed, which involves the transfer of irrigation systems management from state structures to non-governmental organizations. In this case, the transfer of powers and responsibilities from state structures to non-governmental organizations can be carried out with the transition stage of joint management, which is the most rational in the current conditions. Found that the formation of effective management system is impossible without institutionalization of a wide spectrum of forms of partnership relations between different objects of functioning. It is shown that the reforming of irrigation systems management should be carried out on the basis of decentralization with the transfer of water management and water operations to water, this will ensure that water resources and irrigation system infrastructure are managed effectively at the lowest level. The basic directions of improvement of the economic mechanism of development of reclamation are offered.